Meta-evaluation of research in the usage of gamification method in English language teaching - Emine Akkaş Baysal; Hasan Burak İnanç (English Language Teaching Educational Journal, 2022)
This study aimed to evaluate the research in the use of the gamification method in English language teaching. In this study, thirty-eight researches were evaluated. For this purpose, the Council of Higher Education National Thesis Center and Google Academic databases were used to reach research in the use of the gamification method in English language teaching. The sample of this study consisted of twenty-two master's theses, fourteen articles, and two dissertations. The studies were classified and analyzed regarding the type of research, year of publication, method of research, sample, data collection tool and duration of research. Findings show that studies in our country about the subject were primarily at the master's level, and they were carried out using quantitative methods. Findings also show that the number of studies about the subject has been rising only in recent years, and university students were mostly chosen as a sample. Different data collection tools were found to be used in future studies.